Longitudinal association between hippocampus atrophy and episodic‐memory decline in non‐demented APOE ε4 carriers. Issue 1 (28th September 2020) - Gorbach, Tetiana; Pudas, Sara; Bartrés‐Faz, David; Brandmaier, Andreas M.; Düzel, Sandra; Henson, Richard N.; Idland, Ane‐Victoria; Lindenberger, Ulman; Macià Bros, Didac; Mowinckel, Athanasia M.; Solé‐Padullés, Cristina; Sørensen, Øystein; et al.
Abstract: Introduction: The apolipoprotein E ( APOE ) ε4 allele is the main genetic risk factor for Alzheimer's disease (AD), accelerated cognitive aging, and hippocampal atrophy, but its influence on the association between hippocampus atrophy and episodic‐memory decline in non‐demented individuals remains unclear. Methods: We analyzed longitudinal (two to six observations) magnetic resonance imaging (MRI)–derived hippocampal volumes and episodic memory from 748 individuals (55 to 90 years at baseline, 50% female) from the European Lifebrain consortium. Results: The change‐change association for hippocampal volume and memory was significant only in ε4 carriers (N = 173, r = 0.21, P = .007; non‐carriers: N = 467, r = 0.073, P = .117). The linear relationship was significantly steeper for the carriers [t(629) = 2.4, P = .013]. A similar trend toward a stronger change‐change relation for carriers was seen in a subsample with more than two assessments. Discussion: These findings provide evidence for a difference in hippocampus‐memory association between ε4 carriers and non‐carriers, thus highlighting how genetic factors modulate the translation of the AD‐related pathophysiological cascade into cognitive deficits.